2011
DOI: 10.1007/s13437-011-0003-0
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with multicultural human resources in a socially responsible manner: a focus on the maritime industry

Abstract: Shipping companies' crucial need for cost cutting is their main motive for recruiting seafarers of various nationalities and formulating multicultural teams on board ships. This paper seeks to examine ways of dealing with cultural issues by being a socially responsible company. The main point of the research is to examine how managing multicultural crews is related to the shipping companies' and the industry's social responsibility. An extensive literature review on the cultural issues of maritime manpower, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 18 publications
0
35
0
4
Order By: Relevance
“…The MI is a complex, multicultural global industry (Progoulaki and Roe 2011). As Pallis and Ng (2011) highlight, the changing global environment has led to an increasing emphasis on professional, dedicated knowledge within maritime education.…”
Section: The Premise To Flip Teaching: Backward Course Design In Specmentioning
confidence: 99%
See 1 more Smart Citation
“…The MI is a complex, multicultural global industry (Progoulaki and Roe 2011). As Pallis and Ng (2011) highlight, the changing global environment has led to an increasing emphasis on professional, dedicated knowledge within maritime education.…”
Section: The Premise To Flip Teaching: Backward Course Design In Specmentioning
confidence: 99%
“…The practical nature of the MI presents maritime educators (MEs) with an opportunity to expect meaningful student learning that drives teaching practice. Focus should be on how students are learning, what they experience and how they engage in the learning context and subsequently meet graduate attributes which are considered vital by the MI (Wiggins and McTighe 2005;Progoulaki and Roe 2011). The flipped classroom promotes active student engagement and learning, in turn producing more industryready graduates (Strayer 2012; Hannafin et al 1997;Bates and Galloway 2012;Mazur 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The ship's master must learn how to manage multiculturalism. This guarantees a long-term stability in relationships among crew members [12]. On the other hand, physical factors also cause human errors, and the most representative example is the period just before the dawn when surveys showed that many collisions occurred in that period of time.…”
Section: Human Error As Cause Of Marine Accidentmentioning
confidence: 99%
“…There have been a lot of papers such as from [4] to [12] to consider and describe some human and organizational factors that were presented in marine accidents and which can be found in many of them over the years. A neural network applied in [4] has demonstrat-ed its usefulness and accuracy in predicting the type of ship accidents that would occur under different combinations of navigating conditions on the lower Mississippi River.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation